Exploring Adolescents’ Needs in Sexual and Reproductive Health Literacy with Cultural Sensitivity: A Mixed-Methods Study - Masrina Munawarah Tampubolon; Nurhannifah Rizky Tampubolon; niken yuniar sari (Fakultas Ilmu-ilmu Kesehatan, 2026)
Inadequate access to culturally sensitive sexual and reproductive health (SRH) information increases adolescents’ vulnerability to misinformation, risky sexual behaviors, and underutilization of SRH services, particularly in sociocultural contexts where sexuality remains taboo. This study examines sexual and reproductive health literacy (SRHL), risky sexual behaviours and the socio-cultural and institutional factors shaping adolescent SRH experiences. A convergent parallel mixed-methods study was conducted among 994 adolescents aged 11-21 years in Pekanbaru, Indonesia (May-October 2025). Quantitative data were collected using demographic forms, a modified SRHL questionnaire, and a validated Adolescent Sexual Behavior Degree Index, while qualitative data were obtained through focus group discussions and in-depth interviews with teachers, school counselors, healthcare providers, and community leaders. Quantitative data were analyzed descriptively and using chi-square tests, while qualitative data using Colaizzi’s thematic analysis. Most adolescents had inadequate SRHL (92.5%), and 53.3% reported high-risk sexual behaviours. No significant association was found (p = 0.083). Themes included adolescent vulnerability, limited school capacity to address complex adolescent issues; and gaps in educational strategies related to digital media influence, and cultural modernization. These findings highlight the need for culturally grounded, comprehensive SRH education and cross-sector collaboration, with nurses playing a key role in supporting informed adolescent health decision-making.